Physical exercise/sports ameliorate the internet addiction from college students during the pandemic of COVID-19 in China - Cai, Peiling; Wang, Junren; Ye, Peng; Feng, Xiaoming; Yang, Gaoqiang; Huang, Chao; Chen, Xinwei; Hambly, Brett D.; Bao, Shisan; Liang, Shengxiang (Frontiers in Public Health, 2023)
The rapid advancement of modern technology has significantly driven progress in various IT-related activities, resulting in a substantial increase in internet penetration rates, particularly among college students. The utilization of the internet has become one of the most essential tools in our modern society. However, internet addiction (IA) has emerged as a serious concern, particularly among college students, adversely affecting academic performance and having significant psychological and psychiatric implications.The aim of the current study was to determine the impact of physical exercise, gender and academic year on IA among college students.In the present study, we investigated internet usage, engagement in sports activities, and academic performance among college students from Western, Middle, and Eastern regions of Chinese universities. It's noteworthy that most of the respondents were freshmen.Our findings indicate that freshmen students were more susceptible to experiencing IA. Approximately 75% of students engaged in leisure sports activities, revealing an inverse correlation between sports activity and IA. This correlation aligns with the level of sports involvement, emphasizing the potential benefits of physical activity in mitigating IA. However, our study did not uncover any correlation between geographic location and the occurrence of IA, nor did it find differences between medical and non-medical students. Furthermore, our study revealed no significant variations in IA among students from different ethnic backgrounds. The underlying mechanism of IA is being currently determined.Conclusion: Our data suggest that physical exercise, gender, and academic year have a significant impact on IA among college students.